Pengaruh Corporate Social Responsibility (CSR), Profitabilitas, Ukuran Perusahaan terhadap Agresivitas Pajak - Sidiq, Asah Wiari; Adji, Gumawang Dwi Prasetyo (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
Agresivitas pajak ness allows companies to minimize the tax burden borne by the company. This study aims to determine the effect of Corporate Social Responsibility (CSR), Profitability, and company size on Agresivitas pajak ness. In this study Corporate Social Responsibility (CSR), Profitability, and company size on Tax Agressiveness are the independent variables while agresivitas pajak ness is the dependent variable. The results of the analysis show that CSR disclosure and company size have no effect on agresivitas pajak ness, while the profitability variable has a positive effect on agresivitas pajak ness